Survival After MitraClip Treatment Compared to Surgical and Conservative Treatment for High-Surgical-Risk Patients With Mitral Regurgitation. (June 2018) - Kortlandt, Friso; Velu, Juliette; Schurer, Remco; Hendriks, Tom; Van den Branden, Ben; Bouma, Berto; Feldman, Ted; Kelder, Johannes; Bakker, Annelies; Post, Marco; Van der Harst, Pim; Eefting, Frank; et al.
Abstract : Background—: Survival outcome after MitraClip treatment, compared with surgical or conservative treatment, is not well defined. We examined survival after MitraClip treatment in a large multicenter real-life setting. Methods and Results—: We retrospectively formed matched high-risk surgically and conservatively treated control cohorts to compare to a high-risk MitraClip cohort. One thousand thirty-six patients were included in 4 Dutch centers, of which 568 were treated with the MitraClip. The observed survival at 5-year follow-up in our MitraClip cohort was low (39.8%) but was comparable to our conservative cohort (40.5%). Observed 5-year survival for our surgical cohort was 76.3%. However, there were significant differences between the baseline characteristics of the 3 studied cohorts, with the MitraClip cohort having the highest comorbidity burden. After adjusting for baseline differences by using Cox regression, the MitraClip and surgical cohorts showed similar survival ratios (hazard ratio, 0.92; 95% confidence interval, 0.67–1.26; P =0.609), whereas both showed a lower mortality hazard when compared with conservative treatment (hazard ratio, 0.61; 95% confidence interval, 0.49–0.77; P <0.001 and hazard ratio, 0.56; 95% confidence interval, 0.42–0.76; P <0.001, respectively). Conclusions—: This matched analysis suggests a lower mortality hazard for MitraClip intervention in a high-risk population with symptomatic mitral regurgitation when compared with conservative management alone.